2023
DOI: 10.1038/s41594-023-01047-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural conservation of antibiotic interaction with ribosomes

Abstract: The ribosome is a major target for clinically used antibiotics, but multidrug resistant pathogenic bacteria are making our current arsenal of antimicrobials obsolete. Here we present cryo-electron-microscopy structures of 17 distinct compounds from six different antibiotic classes bound to the bacterial ribosome at resolutions ranging from 1.6 to 2.2 Å. The improved resolution enables a precise description of antibiotic–ribosome interactions, encompassing solvent networks that mediate multiple additional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Specific details of the orthosomycins’ interactions with the ribosome were fully described in crystallography and cryo-EM imaging. , A comprehensive view of the orthosomycin binding site on the 50S ribosomal subunit reveal it to be unique from all other ribosomal-targeting natural products . The orthosomycins bind in an extended conformation in the minor grooves of helices 89 and 91 formed by 23S rRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific details of the orthosomycins’ interactions with the ribosome were fully described in crystallography and cryo-EM imaging. , A comprehensive view of the orthosomycin binding site on the 50S ribosomal subunit reveal it to be unique from all other ribosomal-targeting natural products . The orthosomycins bind in an extended conformation in the minor grooves of helices 89 and 91 formed by 23S rRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The A 1 -ring DCIE is conserved among all class I orthosomycins and has been speculated to play a key role in the distinct mechanism of action of everninomicin by forming multiple putative interactions within the pocket formed by ribosomal proteins uL16 and CTC in the 50S subunit . These interactions include potential hydrophobic, ionic, and dipolar interactions, which vary between everninomicin and avilamycin type orthosomycins (Figure C,D). We seek to revitalize the everninomicins as clinical candidates by interrogating these interactions and developing analogs with improved properties. While a total synthesis of Evn A (Ziracin) has been completed, its application to access analogs is challenging as the synthesis consists of over 130 steps. It was demonstrated that the formation of suspended aggregates in formulations of Evn A correlated to adverse reactions, and we hypothesize that the amphipathic nature of Evn A, characterized by alternating hydrophobic and hydrophilic functionality, is a driver of aggregation .…”
Section: Introductionmentioning
confidence: 99%
“…There are three x-ray crystal structures and one cryo–electron microscopy (cryo-EM) structure of clindamycin bound to ribosomes of the diverse bacterial species Deinococcus radiodurans ( 6 ) and Escherichia coli ( 22 , 23 ), as well as the archaeon Haloarcula marismortui ( 24 ), the latter bearing a G2099A (equivalent to A2058 in E. coli ) mutation that permits lincosamide binding. In addition, there are two x-ray crystal structures of IBX bound to wild-type (WT) and Erm-methylated ribosomes of Thermus thermophilus ( 19 ).…”
Section: Design Hypothesis and Synthesis Of A Bridged Macrobicyclic A...mentioning
confidence: 99%
“…(30,31) Antibiotics that bind away from these two hot spots also showed no cross resistance. (30)(31)(32) The activity of avilamycin, which binds in a unique site in the 50S subunit at the entrance to the A-site tRNA accommodating corridor was also not affected by the L7/L12 R76C mutation. (33) In the case of thiostrepton A (34), which targets the L11 protein GTPaseassociated center and is part of the only class of antibiotics known to bind the ribosome in the vicinity of L10/L7 stalk, we also observed no change in MIC for N. gonorrhoeae with the L7/L12 R76C mutation.…”
Section: Oxydifficidin Inhibits Protein Synthesis By Interacting With...mentioning
confidence: 99%